1990
DOI: 10.1105/tpc.2.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Levels and Synthesis of Photosystem II Components in Cyanobacterial Mutants with Inactivated Photosystem II Genes.

Abstract: After interruption or deletion of the photosystem II genes psb8, psbC, and psbD in the cyanobacterium Synechocystis sp. PCC 6803, thylakoids from such mutants were found to be depleted in a number of photosystem II proteins in addition to those for which the gene(s) had been inactivated. Transcript levels of photosystem II genes were measured and protein pulse-labeling was carried out to determine the reason for this effect. Transcripts of all photosystem II genes except the inactivated one(s) were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Means followed by the same letter are not significantly different (Least significant difference test, P < 0.05; Duncan 1955) up-regulated in various photosystem II mutants. For example, the transcript number of psbA was higher in the psbC mutant (psbC -), the expression of psbDI/DII increased in the psbB -mutant, and the expression of psbB increased in the psbDI/DIImutant (Yu and Vermaas 1990). For rps19, there was no difference in gene copy number between the albino mutants and the wild type, but the number of transcripts was lower in the mutants, or undetectable (Fig.…”
Section: Forwardmentioning
confidence: 86%
“…Means followed by the same letter are not significantly different (Least significant difference test, P < 0.05; Duncan 1955) up-regulated in various photosystem II mutants. For example, the transcript number of psbA was higher in the psbC mutant (psbC -), the expression of psbDI/DII increased in the psbB -mutant, and the expression of psbB increased in the psbDI/DIImutant (Yu and Vermaas 1990). For rps19, there was no difference in gene copy number between the albino mutants and the wild type, but the number of transcripts was lower in the mutants, or undetectable (Fig.…”
Section: Forwardmentioning
confidence: 86%
“…However, some CP47, D1, and D2 could be detected by western blotting, along with relatively normal levels of CP43. In all PSII mutants analyzed thus far, the reason for depletion of selected PSII proteins from the membrane has been found to be an increased turnover of these proteins rather than an inhibition of transcription or translation [ 31 ]. Therefore, it is reasonable to assume that in the A(G351-T365) mutant the decreased levels of CP47, D1 and D2 are caused by a decreased stability of these proteins in the thylakoid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence emission spectra were recorded on a SPEX Fluorolog 2 scanning spectrometer. Thylakoids were prepared as described by Yu and Vermaas [31]. Methods used for sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and western blotting are described in Vermaas et al [22].…”
Section: Mutant Characterizationmentioning
confidence: 99%
“…In addition to the expected absence of the a-subunit of cyt 5559, we found that thylakoids of CP6t16 do not contain significant amounts of D2. The presence of the CP43 protein, encoded by the psbC gene, implies that the dicistronic transcript for the psbDi/C gene cluster is present in CP6t16 {Yu and Vermaas, 1990). Thus, it is possible that the psbDi gene product, D2, is synthesized and then rapidly turned over in this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants without CP43 accumulate reaction centres at approximately 10% of the wild-type conoentration (Vermaas et ai, 1988;Rdgner et ai, 1991). Inactivation of the psbD gene, coding for the D2 protein, results in the loss of Dl, CP47 and CP43 (Vermaas et ai, 1988;Yu and Vermaas, 1990). Additionally, mutation of specific residues in the D2 protein, predicted to bind a quinone cofactor Q^, leads to destabilization of the PSIl complex (Vermaas et ai, 1990).…”
Section: Introductionmentioning
confidence: 99%